Populasi dan Status Regenerasi Taxus sumatrana di Hutan Lindung Gunung Dempo: Implikasi Terhadap Praktek Konservasi - Denny, Denny; Susilo, Adi (Universitas Sebelas Maret, 2022)
Exploration to find a new population of Taxus sumatrana in the unexplored Gunung Dempo Protected Forest, South Sumatera was conducted in 2014. T. sumatrana, a protected species of medicinal plant, was looked for by following the hiking trails of Rimo and Kampung IV up to a height of 2.133 m asl. A total of 13 trees of T. sumatrana were found at an altitude between 1.853 m and 2.133 m asl, with a diameter at breast height ranging from 22 cm to 120 cm. T. sumatrana seedlings or saplings were not found, confirming that these plants regenerate very poorly. Low natural regeneration is caused by a variety of factors, including the scarcity of female trees, a lack of light, an absence of suitable microsites, seed predation, and browser stress. Poor regeneration may cause a seedling establishment to fail, which will have an effect on the T. sumatrana tree demographics. Even though the habitat of T. sumatrana is in proper legal status, namely Mount Dempo Protected Forest, if no intervention is taken, this protected plant species may go extinct locally. T. sumatrana's natural regeneration is complicated. Therefore, it is essential to carry out an intervention to foster the seedling population so that it can continue to become a new regeneration. We must actively intervene, particularly through silvicultural intervention, in order to protect and conserve T. sumatrana.